PENGARUH KEJELASAN SASARAN ANGGARAN DAN SISTEM PENGENDALIAN INTERN TERHADAP AKUNTABILITAS KINERJA AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Survei Pada Satuan Kerja Perangkat Daerah (SKPD) Kabupaten Parigi Moutong) - Fitrawati, Fitrawati (Katalogis, 2017)
This study aimed to examinethe effect of Simultaneous and partial clarity budgetary targets and internal control system toward the accountability of Government Performance. Population and sample of the study was 35 SKPD in Parigi Moutong District. The research data collection using questionnaire survey. The technique of data analysis used multiple regression analysis by using Statistical Package for Social Science (SPSS) program. The results of this study indicate that the budget goal clarity and internal control system effect of the performance accountability of government agencies. Partially, clarity of budget targets and internal control system positively and significantly influence officials performance accountability.